2021
DOI: 10.5603/arm.a2021.0024
|View full text |Cite
|
Sign up to set email alerts
|

Miniforceps EBUS-Guided Lymph Node Biopsy: Impact on Diagnostic Yield

Abstract: Introduction: Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is the standard diagnostic method for sampling mediastinal and hilar lymph nodes. Non-diagnostic samples have led some pulmonologists to add a miniforceps biopsy (EBUS-TBFB) in order to increase diagnostic yield. Our study aims to analyze the impact of adding EBUS-TBFB to the EBUS-TBNA in cases where Rapid On-site Evaluation (ROSE) was negative for malignancy or was non-diagnostic. Material and methods: This retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…These high figures have been confirmed both for cytopathological diagnosis and for molecular assays 6 . Recent reports have incorporated a new diagnostic tool in the management algorithms to reduce the rate of false negatives or inadequate samples by EBUS‐TBNA with ROSE, the miniforceps EBUS‐guided biopsy, which seems to increase the number of diagnostic samples between 12% and 27%, but mainly for lymphoma and granulomatous diseases and not so much for NSCLC 7 …”
Section: Improvements In Bronchoscopic Accessmentioning
confidence: 87%
See 1 more Smart Citation
“…These high figures have been confirmed both for cytopathological diagnosis and for molecular assays 6 . Recent reports have incorporated a new diagnostic tool in the management algorithms to reduce the rate of false negatives or inadequate samples by EBUS‐TBNA with ROSE, the miniforceps EBUS‐guided biopsy, which seems to increase the number of diagnostic samples between 12% and 27%, but mainly for lymphoma and granulomatous diseases and not so much for NSCLC 7 …”
Section: Improvements In Bronchoscopic Accessmentioning
confidence: 87%
“…6 Recent reports have incorporated a new diagnostic tool in the management algorithms to reduce the rate of false negatives or inadequate samples by EBUS-TBNA with ROSE, the miniforceps EBUS-guided biopsy, which seems to increase the number of diagnostic samples between 12% and 27%, but mainly for lymphoma and granulomatous diseases and not so much for NSCLC. 7 Some recent advances, like virtual bronchoscopic and electromagnetic navigation (EMN), have improved the diagnostic yield of traditional bronchoscopy, but mainly for the diagnosis of small peripheral lesions. 8 Recent studies on EMN report a diagnostic yield close to 70%, that remains lower than the one reached by transthoracic needle aspiration (over 90%).…”
Section: Ebus-fnac Is Usually Performed On An Outpatient Basis Undermentioning
confidence: 99%
“…Out of the non-diagnostic TBNA samples on rapid on side evaluation (ROSE) and cell block, subsequent TBFB sampling resulted in additional pathological diagnosis in 16% of the cases; 67% of these were non-caseating granulomas. No complications were reported [ 29 ].…”
Section: Procedure-related Technical Factors and Their Effects On Diagnostic Yieldmentioning
confidence: 99%
“…Currently available mini-forceps include the Olympus mini-forceps (FB-56D-I; Olympus Ltd., Tokyo, Japan) with an outer diameter of 1.15 mm and a cup opening of 7.3 mm [ 27 ], the Boston Scientific “SpyBite biopsy” Forceps (model: M00546270, Natick, MA, USA) with an outer diameter of 1 mm [ 29 ], and the CoreDx™ Pulmonary Mini-Forceps by Boston Scientific with an outer diameter of 0.96 mm and a 4.3 mm jaw opening ( Figure 2 ). The specimen obtained by EBUS-TBFB should be handled as the histology specimen and placed in formalin for fixation or in saline if culture is required [ 31 ].…”
Section: Procedure-related Technical Factors and Their Effects On Diagnostic Yieldmentioning
confidence: 99%
“…With the linear EBUS bronchoscope miniforceps biopsy (MFB) can be passed in real time into the mediastinal and hilar lymph nodes through a previously established tract after TBNA sampling. Shiari et al showed that MFB to be useful adjunctive tool in the diagnosis of non-malignant conditions with the potential to spare patients more invasive surgical procedures ( 6 ). Our aim in this retrospective study was to determine the diagnostic yield of EBUS-guided MFB (EBUS-MFB) compared to EBUS-TBNA at our institution in both malignant and nonmalignant conditions to examine if performing MFB after TBNA had any effect on the diagnostic yield.…”
Section: Introductionmentioning
confidence: 99%